Changes in Global Trade Patterns and Women's Employment in Manufacturing, 1995–2011. Issue 3 (3rd July 2018) - Saraçoğlu, Dürdane Şirin; Memiş, Emel; Voyvoda, Ebru; Kızılırmak, Burça
ABSTRACT: This study investigates the feminization and defeminization trends in manufacturing employment in thirty countries from 1995 to 2011. Utilizing two separate methods, structural decomposition analysis (SDA) and factor content analysis (FCA), the study identifies the major industries and trade partners behind the structural shifts in trade that have induced changes in employment and thus in the rates of women's employment. The findings highlight that, as a general trend, defeminization in manufacturing has persisted in the Global North, led by a negative trade impact in low-technology industries. In the Global South, feminization and defeminization trends are not as straightforward. Despite positive changes in women's share of employment in medium-high- and high-technology industries, negative gender bias effects of trade changes are found particularly in high-technology industries, where occupations are notably gendered.